2010
DOI: 10.1111/j.1438-8677.2010.00389.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the AtSUC1 gene in the female gametophyte, and ecotype‐specific expression differences in male reproductive organs

Abstract: Based on analyses in Arabidopsis thaliana ecotype C24, the AtSUC1 protein was previously characterised as a male gametophyte-specific H(+)/sucrose symporter. Later, expression analyses in ecotype Columbia-0 (Col-0) identified AtSUC1 expression also in trichomes (not detected in trichome-less C24 plants) and roots, suggesting ecotype-specific differences in AtSUC1 expression. Here, we present data on additional ecotype-specific differences in AtSUC1 expression in other tissues. Using different AtSUC1 promoter-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 31 publications
1
26
0
1
Order By: Relevance
“…However, after fertilization, the developing embryo remains symplasmically isolated from the mother tissues, and further transport of photoassimilates is attained with specific transporters and carriers Werner et al, 2011;Chen et al, 2015b). Here, the expression of SUC1, SUC8, and SUC9 genes has been detected Feuerstein et al, 2010), although the differential expression of the SUC1 transporter observed in Arabidopsis ecotypes suggests functional redundancy. In the ovule, the synergid cells that surround the egg also are metabolically very active.…”
Section: Carbohydrate Partitioning and Metabolism In Floral Organsmentioning
confidence: 84%
“…However, after fertilization, the developing embryo remains symplasmically isolated from the mother tissues, and further transport of photoassimilates is attained with specific transporters and carriers Werner et al, 2011;Chen et al, 2015b). Here, the expression of SUC1, SUC8, and SUC9 genes has been detected Feuerstein et al, 2010), although the differential expression of the SUC1 transporter observed in Arabidopsis ecotypes suggests functional redundancy. In the ovule, the synergid cells that surround the egg also are metabolically very active.…”
Section: Carbohydrate Partitioning and Metabolism In Floral Organsmentioning
confidence: 84%
“…ATSUC2 is involved in loading sugar from the apoplast to conductive elements [33]. F14P1.2, AT1G19650, a Sec14p-like phosphatidylinositol transfer family protein, is linked to the upregulated AT1G22530, a patellin 2 transporter (Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, Arabidopsis lines were generated and analysed that had SUC2, their companion cell-specific phloem loader, replaced either with SUC1, another Arabidopsis sucrose transporter that is usually expressed in pollen, anther connective tissue, developing ovules, or roots of seedlings (Stadler et al , 1999; Sivitz et al , 2008; Feuerstein et al , 2010), or with Srt1 from the corn smut fungus U. maydis (Wahl et al , 2010). Transcription and translation of the transgenes were followed by RT-PCR and with specific antisera, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Analogously, purification of available anti-SUC1 raw serum (αSUC1) was done using a synthetic peptide (Feuerstein et al , 2010). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation